KEBIJAKAN PENJAMINAN MUTU UNIVERSITAS RIAU DALAM PENGEMBANGAN KUALITAS TENAGA PENDIDIK TAHUN 2010-2014 - Budi Sutanto; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Institute for the Development and Quality Assurance of Education, University of Riau has the task of coordinating, implementing, monitoring, and evaluation of improvement activities and the development of learning and education quality assurance University of Riau. Less serious Riau University in developing educators, where the lack of seriousness with the phenomenon: lack of development road map educators, lack of coordination between units in the development of educators development of educators partial (not complete), lack of competence map educators University of Riau and not the division of labor in a unit in the development of educators.The purpose of this study is to investigate the implementation of quality assurance policies Riau University in the development of the quality of teachers from 2010 to 2014 and to identify obstacles in the implementation of quality assurance policies Riau University in the development of the quality of teachers 2010-2014. In this study the authors used qualitative methods and this paper outlines in a descriptive way. In gathering research data, the data collection techniques used were interviews and documentation.The results of this study concluded that quality assurance policy Riau University in the development of the quality of teachers 2010-2014 has not done well because in addition to lack of support also their educators who join the training is placed in a different position so that experienced problems in its development. Obstacles in the implementation of quality assurance policies Riau University in the development of the quality of teachers 2010-2014: (1) awareness is still lacking lecturers and employees, (2) Limited facilities and infrastructure, and (3) Budget less.Keywords: Policy, Quality Assurance, Quality